Does Financial Flexibility Matter for Firm’s Finance Policy? Evidence from Swedish High -Tech Firms: Case Study of Ericsson - Al-Shakrchyai, Eatessam; Alnassar, Walaa Ismael (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This paper explores why high-tech firms with high credit quality are more likely to have external finance, and if the securing funding is related to financial flexibility. Many earlier studies have shown that it is valuable for firms to choose financial policies that keep financial flexibility to respond to negative shocks in the form of unexpected periods of insufficient resources. However, the complexity and unpredictability in high?tech business make the flexibility in finance more valuable to face an increasingly unpredictable environment and to grow into a hugely profitable. Degree of financial flexibility has estimated in three different models based on leverage to investigate whether the flexibility degree affects the company’s ability and to find out the driving factor in financial flexibility indicators. By using financial data from annual reports of the Swedish multinational networking and telecommunications company “Ericson” during the period 2007 to 2016, the results provide evidence that the high-tech company has a high access to capital markets due to its low leverage and keeping an equity ratio over 45% which supporting the hypothesis that financial flexibility matter and has influence on the firm’s ability to get access and restructure its financing.